ANALISIS TINGKAT PENGANGGURAN TERBUKA (TPT) PROVINSI RIAU - Hilwa Hilmana; Makrifatul Khasanah; Sri Ningsih (Jurnal Riset Multidisiplin Edukasi, 2026)
The Open Unemployment Rate (TPT) in Riau Province exhibited fluctuating dynamics during the 2016–2025 period. This study evaluates the influence of the region's commodity-based economic structure on labor absorption. Using a descriptive-analytical method, the study found that Riau has high labor elasticity in the manufacturing sector. Despite being impacted by the global crisis in 2020, Riau's recovery has been one of the fastest in the Sumatra region, with the TPT reaching a low of 3.7% in 2024.